Low Dose Ketamin - Wiryana, Made; Sinardja, I Ketut; Budiarta, I Gede; Agung Senapathi, Tjokorda Gde; Widnyana, Made; Aryabiantara, I Wayan; Utara Hartawan, I Gusti Agung Gede; Parami, Pontisomaya; Novita Pradnyani, Ni Putu; Putra Pradhana, Adinda (Bali Journal of Anesthesiology, 2017)
Ketamine binds non-competitive against a phencyclidine receptors bound N-methyl-D-aspartate (NMDA), a receptor that is involved in the pathophysiology of acute pain. Ketamine has been used as an intravenous anesthesia, analgesia for acute and chronic pain at a dose of subanaesthetic. Ketamine is a dissociative anesthetic produces a state with a characteristic strong analgesia, amnesia, and catalepsy. Dissociative components resulting from the effect on the limbic system and talamoneokortikal. Low-dose ketamine as known as analgesia dose ketamine or subanestesia dose is 0.2 to 0.75 mg / kg IV. At low doses, ketamine does not increase the effect psikomimetik like dissociation or deep sedation. The combination with midazolam provides satisfactory sedation, amnesia and analgesia without significant cardiovascular depression.